The Role of Classroom Management in Enhancing Elementary Students' Mathematics Learning Motivation - Hendarsyah, Jelita Dewanty; Komara, Endang (Papanda Publisher, 2025)
Mathematics learning motivation remains a significant challenge in elementary education, with many students experiencing difficulties and low engagement. Classroom management has been identified as a critical factor influencing student motivation, yet limited research has examined this relationship specifically in elementary mathematics contexts. This study aimed to analyze the role of classroom management in enhancing elementary students' mathematics learning motivation. A qualitative case study was conducted in one Grade VI classroom at a public elementary school in Cianjur Regency, Indonesia. Data were collected over three months through semi-structured interviews with teachers and students, non-participant observations of 24 mathematics lessons, and document analysis. Data analysis followed Creswell's framework involving data reduction, display, and conclusion drawing using inductive and deductive coding approaches. The analysis revealed a four-phase classroom management implementation model: planning, implementation, monitoring, and follow-up. Systematic planning included deliberate classroom arrangements and differentiated instruction strategies. Implementation involved consistent positive reinforcement (100% of sessions), student choice opportunities (75%), and real-world mathematics connections (87.5%). Monitoring demonstrated teacher responsiveness to student engagement cues, while follow-up ensured sustained motivational support. Quantitative indicators showed 15% improvement in homework completion and 12% increase in voluntary participation. The findings support theoretical frameworks emphasizing classroom management's multifaceted nature and demonstrate that systematic approaches significantly enhance student motivation. The four-phase model extends previous research by providing specific mechanisms through which classroom management influences mathematics learning motivation at the elementary level, addressing gaps in existing literature focused primarily on secondary education.